Diagnostic Pitfalls in Newborns and Babies with Blisters and Erosions - Elke Nischler; Alfred Klausegger; Clemens Hüttner; Gabriele Pohla-Gubo; Anja Diem; Johann W. Bauer; Helmut Hintner (Dermatology Research and Practice)
Establishing the correct diagnosis in newborns presenting with blisters and erosions is not always a straightforward process. Many different disease entities including acquired (i.e., infectious, immunobullous, traumatic) and inherited disorders have to be taken into consideration. Similarities in clinical appearance, colonization and/or superinfections of preexisting skin lesions, as well as the absence of late changes in the neonate often pose significant diagnostic challenges. In this paper we discuss by giving examples the process of making an accurate diagnosis of blistering skin diseases in the neonatal period on the basis of a diagnostic algorithm. In addition, we provide an overview of the rational use and the limitations of laboratory procedures such as microbial testing, routine light microscopy, immunofluorescence antigen mapping, transmission electron microscopy, and molecular genetic analysis.